2016
DOI: 10.21566/tarbitderg.281866
|View full text |Cite
|
Sign up to set email alerts
|

Pamuk (Gossypium hirsitum L.)’da Yabancı Ot Kontrolü İçin Kritik Periyodun Belirlenmesinde Sıra Arası Mesafesi Etkilerinin Araştırılması

Abstract: ÖzArazi çalışmaları pamukta yabancı ot kontrolünde kritik periyodun belirlenmesinde üç farklı sıra arası mesafenin (50, 70 ve 90 cm) etkilerinin araştırılması için 2012-2013 yıllarında Kahramanmaraş Doğu Akdeniz Geçit Kuşağı Tarımsal Araştırma İstasyonu'na ait arazide yapılmıştır. Dört parametreli log-logistik model yabancı otlu ve yabancı otsuz periyodun kültür bitkisi veriminin oransal değerlerine göre dönüştürülmüştür. Pamuğun oransal verimi sıra arası mesafe göz önünde bulundurulmaksızın yabancı otlu yada … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…It is reported that an effective weed control application is required in the critical period of 2-3 weeks to 7-10 weeks followed by crop emergence (Gunes et al 2008, Kaya and Nemli 2003, Tursun et al 2016, Uludag et al 2004, Uludag et al 2012, Vargas et al 1996. Moreover, some invasive plants such as Ipomoea triloba L. and Amaranthus palmeri L., appear as weeds that cause problems in agricultural and non-agricultural fields (Üremiş et al 2020).…”
mentioning
confidence: 99%
“…It is reported that an effective weed control application is required in the critical period of 2-3 weeks to 7-10 weeks followed by crop emergence (Gunes et al 2008, Kaya and Nemli 2003, Tursun et al 2016, Uludag et al 2004, Uludag et al 2012, Vargas et al 1996. Moreover, some invasive plants such as Ipomoea triloba L. and Amaranthus palmeri L., appear as weeds that cause problems in agricultural and non-agricultural fields (Üremiş et al 2020).…”
mentioning
confidence: 99%